(De)Constructing the Disruption: Enacted Sensemaking and Sensegiving in Institutionally Plural Fields - Kumar Amal; Higgins Monica C. (Journal of Organizational Sociology)
If an event happens in the woods, and nobody responds to it, is it a disruption? In this paper, we address a gap in the organizational sociology literature about how events are constructed as “institutional disruptions” in institutionally plural fields. We integrate the disconnected literatures of sensemaking/sensegiving and institutional pluralism to argue that institutional disruptions in institutionally plural fields are not coterminous with exogenous events, but rather are the result of a process of fieldwide sensemaking and sensegiving mediated by intermediary organizations. We use the American higher education community’s response to the Trump administration’s 2017 ‘travel ban’ as a paradigmatic example that illuminates these dynamics with some clarity. In particular, we illuminate the relationships between conditions of institutional pluralism, extra-field events, the social construction of meaning within fields, the role of intermediary organizations, and the nature of organizational actions in response. Emerging from our theoretical exploration, we offer implications and avenues for future research for organizational sociologists. Collectively, our theorizing opens the door for scholars to re-examine previously taken-for-granted assumptions about disruptions and better theorize the earliest moments of institutional change.